2010
DOI: 10.1155/2010/569215
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Decrease during Glycemic Control in Type 2 Diabetes

Abstract: Purpose. To assess an effect of glycemic control on retinal nerve fiber layer (RNFL) in type 2 diabetes mellitus. Methods. Thirty-eight eyes of 38 patients with type 2 diabetes undergoing blood glucose regulation were enrolled. All patients were examined at (1) initial visit, (2) 1 month, (3) 2 months, and (4) 4-month after the initial examination. On each occasion, glycosylated hemoglobin (HbA1c) levels and optical coherence tomography (OCT) scanning for RNFL thickness were evaluated. 360 degree circular OCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
(26 reference statements)
5
14
0
2
Order By: Relevance
“…Higher glycaemic levels have been reported to be related to development and progression of retinopathy in the Diabetes Control and Complications Trial (DCCT) and in the Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR); however, acute or rapid reductions in HbA 1c levels were associated with worsening of DR . Also, after 4 months of strict metabolic control, RNFL thickness reduced further compared to baseline values . The findings reported in previous studies and that from our study may indicate (1) a nonlinear relationship between retinal tissue thickness and HbA 1c levels, and (2) the extent or the percentage of reduction in glycaemic levels may be equally important, in addition to absolute HbA 1c levels.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Higher glycaemic levels have been reported to be related to development and progression of retinopathy in the Diabetes Control and Complications Trial (DCCT) and in the Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR); however, acute or rapid reductions in HbA 1c levels were associated with worsening of DR . Also, after 4 months of strict metabolic control, RNFL thickness reduced further compared to baseline values . The findings reported in previous studies and that from our study may indicate (1) a nonlinear relationship between retinal tissue thickness and HbA 1c levels, and (2) the extent or the percentage of reduction in glycaemic levels may be equally important, in addition to absolute HbA 1c levels.…”
Section: Discussionsupporting
confidence: 73%
“…The association between HbA 1c levels and duration of diabetes with inner retinal thickness has been investigated, revealing a reduction in the RNFL thickness after 4 months of strict control of HbA 1c levels . An inverse correlation has been reported between duration of diabetes and retinal tissue thickness .…”
Section: Introductionmentioning
confidence: 99%
“…Another study found the superior quadrant to be more predisposed to damage and a higher rate of cellular death, which resulted in RNFL thinning [26]. Our study demonstrated a lack of thinning of the RNFL at the nasal quadrants.…”
Section: Discussionsupporting
confidence: 47%
“…11 On the other hand, another study reported that RNFL thickness decreased after 4 months of glycemic control, which was explained by the transient deterioration of diabetic retinopathy following intensive glycemic control. 12 In this study, among a number of parameters evaluated, cube average thickness, average GCIPL, inferonasal GCIPL, inferior GCIPL, and inferotemporal GCIPL thickness parameters measured in the macular area were positively correlated with HbA 1c levels at the time of OCT examination. Retinal changes in DM can be due to a variety of pathways involving several factors.…”
Section: Effect Of Glycosylated Hemoglobin Levels On Retinal Changesmentioning
confidence: 67%